Investigating parents’ food-provision behaviours via the sensitisation method - Pettigrew, Simone; Pescud, M. (Elsevier BV, 2013)
In this article, the sensitisation method is introduced as an approach suited to investigating nutritionrelated issues affecting disadvantaged families. Using a longitudinal design, sensitisation is a combination of self-introspection, memory work, observation, individual interviews, and focus groups. The method was applied to child obesity as experienced in low socioeconomic families to generate information about parents’ food provision attitudes and behaviours. Data were collected in Western Australia between May 2010 and May 2011. The outcome was a large quantity of data that provided deep insight into the foodrelated experiences of parents of overweight children. The growing awareness produced by the sensitisation process also resulted in reported behavioural change in many of the study participants, thus indicating that the method may effectively constitute an intervention in its own right.